2020
DOI: 10.1167/tvst.9.7.26
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Mechanical Anisotropy of the Cornea Using Brillouin Microscopy

Abstract: The purpose of this study was to detect the mechanical anisotropy of the cornea using Brillouin microscopy along different perturbation directions. Methods: Brillouin frequency shift of both whole globes (n = 10) and cornea punches (n = 10) were measured at different angles to the incident laser, thereby probing corneal longitudinal modulus of elasticity along different directions. Frequency shift of virgin (n = 26) versus cross-linked corneas (n = 15) over a large range of hydration conditions were compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
8
0
2
Order By: Relevance
“…In isotropic tissues such as the crystalline nucleus, this measurement of compressibility can also be converted into the surface parallel (transverse) E-module. However, as described above, the cornea is significantly more anisotropic than the lens 26 , and, therefore the measured surface perpendicular E-module of the cornea, should not, as done by Scarcelli et al, be misinterpreted as a equivalent to the surface-parallel E-module.…”
Section: Application On the Human Eyementioning
confidence: 90%
See 2 more Smart Citations
“…In isotropic tissues such as the crystalline nucleus, this measurement of compressibility can also be converted into the surface parallel (transverse) E-module. However, as described above, the cornea is significantly more anisotropic than the lens 26 , and, therefore the measured surface perpendicular E-module of the cornea, should not, as done by Scarcelli et al, be misinterpreted as a equivalent to the surface-parallel E-module.…”
Section: Application On the Human Eyementioning
confidence: 90%
“…Diese Komprimierbarkeitsmessung kann in isotropen Geweben wie dem Linsenkern auch in den oberflächenparallelen (transversalen) E-Modul umgerechnet werden. Da die Hornhaut, wie oben beschrieben, biomechanisch deutlich stärker anisotrop als die Linse ist [26], sollte der gemessene oberflächensenkrechte E-Modul der Hornhaut, jedoch nicht wie von Scarcelli et al als Pendant zum oberflächenparallelen E-Modul missinterpretiert werden. Andererseits lässt der gemessene longitudinale Modul Rückschlüsse auf den axialen Verlauf der Festigkeit der Hornhaut zu [18] und damit konnte auch der Einfluss der Hydratisierung der Hornhaut quantitativ studiert werden [12,27].…”
Section: Anwendung Am Menschlichen Augeunclassified
See 1 more Smart Citation
“…In this case, using a backscattering configuration, where θ = 180°, sin nobreak0em.25em⁡ θ 2 = 1 , and the formula becomes v normalB = 2 n λ M ρ This means that the longitudinal modulus M can be calculated from the measured frequency shift M = ρ true( v normalB λ 2 n true) 2 . The frequency shift was measured using a Brillouin microscope set up similar to the one used in previous studies. ,,, An inverted confocal microscope, with a 660 nm continuous wave laser (Torus, Laser Quantum) with a power ∼30 mW was focused onto the sample by an objective lens (40×/0.6NA, Olympus), with a transverse resolution of ∼0.4 μm and an axial resolution of ∼2.6 μm. The backscattered light was collected by the same objective and coupled into the Brillouin spectrometer, composed of two-stage virtually imaged phase array (VIPA) etalons.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study determined that the Brillouin microscope can measure the solid, or stromal, mechanical properties of the cornea, independent of hydration. The contribution of hydration to the Brillouin shift was isolated, and it was found that cross-linking results in an increased Brillouin shift due to changes in the solid mechanics of ex vivo porcine corneas [67].…”
Section: Brillouin Microscopymentioning
confidence: 99%